The Economic Impacts of Government Spending Cut: The Case of Indonesia - KUNCORO, Haryo; PAMBUDI, Daniel; PAMBUDI, Daniel (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
This paper attempts to analyze the impact of fiscal policy on the macroeconomic performance in Indonesia. Using CGE EMERALD (Computable General Equilibrium Model with Economic Regional Analysis Dimensions), we simulate the impact of 1 percent deficit reduction (i.e. government expenditures cut) on macroeconomic variables both in national and regional levels. The overall simulations show that the decrease in government expenditures has positive impacts on real private investment expenditures and export volume as well as aggregate capital stock. Also, the decrease in government expenditures reduces import volume higher than that of export. In relation to employment, the negative impact is marginally only on the non-tradable sectors. Those findings imply that not all government expenditures are productive in nature. Hence, they perform the feasibility of government policy to reduce the government spending and conduct balance budget as well as counter-cyclical policies in the future not only to maintain economic growth in general but also balance of payment and fiscal sustainability in particular.